Manajemen Strategi Organisasi Internal Kampus dalam Meningkatkan Kemampuan Komunikasi Dan Prestasi Akademik Mahasiswa STIT Palapa Nusantara - Kamaruddin; Khairil Anwar; Mulya Agustin (Pendidikan Al-Gafari, 2024)
Organization is a system of each other influence between insider working groups The same for reaching the objective. One's position leader organization has a very important role because own task as taker decisions for the continuity of the organization he leads. Study this aim for know implementation of internal and external environment campus College of Science Tarbiyah Palapa Nusantara, campus internal organizational strategy in increasing ability communication students, and internal campus strategies in increasing performance academic student. Study This is a study, Analysis of collected data with observation, interviews, and documentation. Research results show that the implementation of internal and external environments in internal campus organizations has strengths in the form of doing UKM activities (activity unit students), and writing work scientific, weaknesses or weaknesses in the form of the difficulty of proposals for applying for funds in activity organization, opportunities in the form of support from party campus, threat or threats in the form of less parental support in organize. Improving strategy ability communication by conducting discussion programs and providing a chance for opinions, and strategies to improve performance academic by running a language UKM program in English and language Arabic, design graphics, and writing work.